Impacts of Red Imported Fire Ants on Northern Bobwhite Nest Survival - Angelina M. Haines; D. Clay Sisson; Robert A. Gitzen; Christopher A. Lepczyk; William E. Palmer; Theron M. Terhune II (National Quail Symposium Proceedings, 2017)
Invasive species are a large management issue because of extensive environmental and economic damage. The red imported fire ant (RIFA, Solenopsis invicta) is an invasive species of growing concern in wildlife management in the United States because of its increasing distribution, difficulty to suppress, and aggressive predation on native invertebrates, herpetofauna, birds, and small mammals. Managers of the northern bobwhite (Colinus virginianus) have questioned the direct impact of RIFA on bobwhite nest success, particularly the factors that might influence the level of nest predation. We hypothesized that RIFA predation on northern bobwhite would vary by location and correlate with drier weather conditions. To test our hypothesis we analyzed bobwhite nest data gathered from 3 properties in the southeastern United States. The nest data are part of a larger research effort on bobwhites, collected by Tall Timbers Research Station and the Albany Quail Project using radiotelemetry from 1992 to 2015. Over these 23 years we tracked bobwhites and located nests (n = 3,207) daily to determine nest fate (success or failure) based on field sign and evidence attributed to specific causes of mortality. We used the nest-survival model in Program MARK to estimate nest survival. Average nest survival varied annually for the Albany and Tall Timbers study areas, respectively. The overall effect of RIFAs on nest survival was generally small, with an average annual loss in Albany of 5.13% (range = 0–15.59%) and 2.17% in Tall Timbers (range = 0–5.83%), but in some years was as high as 15.6%. Greater losses occurred late in the breeding season when it was typically drier and the loss rate in general was higher on the drier of the 2 study sites. Despite the relatively small direct impact on nesting success demonstrated, indirect effects of RIFAs on bobwhite populations are poorly understood at present. Quantifying the influence of indirect factors, such as soil type and habitat disturbance, on RIFA abundance and the subsequent impact on bobwhites, will provide additional insight to the ecological interaction with a highly pervasive and expanding invasive species and help inform management options.
Keywords: colinus virginianus; northern bobwhite; drought; gamebird management; invasive species; KBDI; Keetch-Byram Drought Index; nest predation; quail